Topological Indices for Inverse Graphs Associated With Finite Cyclic Group - Gopinath, S.; Doss, A. Richard Praveen; Kalaimurugan, G. (Communications in Mathematics and Applications, 2023)
Topological indices are mathematical descriptors for molecular structures. These descriptors are used to describe physico-chemical properties such as solubility, molecular shape and molecular weight. In this paper, we present distance-based topological indices such as Wiener index and hyper-Wiener index by using Hosoya polynomial for inverse graphs associated with finite cyclic group. Also, we have found eccentricity based topological index of inverse graphs associated with finite cyclic group.